Case Study of Community Participation in Chemical Waste Management in Urban Areas - Sri Yunita; Putri Khairi Izwani; Cinta Febby Dewita; Amelia Syafitri; Indri Wahyuni; Zakia Diani Rangkuti (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
This study examines community participation in chemical waste management in urban areas, aiming to understand the extent of community involvement in protecting the environment from the harmful impacts of hazardous waste. The introduction outlines the importance of managing chemical waste in densely populated urban areas and the risks arising from a lack of public awareness and knowledge. This research employs a qualitative approach, utilizing in-depth interviews, questionnaires, and direct observations. Interviews were conducted to explore community perspectives and motivations, questionnaires were used to assess their level of participation and understanding, and observations were carried out to examine real actions in waste management practices. The results indicate that community participation remains low, influenced by limited outreach, awareness, and support facilities. This study highlights the need for improved education, facility provision, and partnership programs between the government, community, and private sector for more effective and sustainable chemical waste management.